Balloon kyphoplasty in the management of vertebral compression fractures: an updated systematic review and meta-analysis - Taylor, Rod S. (Springer-Verlag, 2007)
This systematic review updates the understanding of the evidence base for balloon kyphoplasty (BKP) in the management of vertebral compression fractures. Detailed searches of a number of electronic databases were performed from March to April 2006. Citation searches of included studies were undertaken and no language restrictions were applied. All controlled and uncontrolled studies were included with the exception of case reports. Prognostic factors responsible for pain relief and cement leakage were examined using meta-regression. Combined with previous evidence, a total of eight comparative studies (three against conventional medical therapy and five against vertebroplasty) and 35 case series were identified. The majority of studies were undertaken in older women with osteoporotic vertebral compression fractures with long-term pain that was refractory to medical treatment. In direct comparison to conventional medical management, patients undergoing BKP experienced superior improvements in pain, functionality, vertebral height and kyphotic angle at least up to 3-years postprocedure. Reductions in pain with BKP appeared to be greatest in patients with newer fractures. Uncontrolled studies suggest gains in health-related quality of life at 6 and 12-months following BKP. Although associated with a finite level of cement leakage, serious adverse events appear to be rare. Osteoporotic vertebral compression fractures appear to be associated with a higher level of cement leakage following BKP than non-osteoporotic vertebral compression fractures. In conclusion, there are now prospective studies of low bias, with follow-up of 12 months or more, which demonstrate balloon kyphoplasty to be more effective than medical management of osteoporotic vertebral compression fractures and as least as effective as vertebroplasty. Results from ongoing RCTs will provide further information in the near future.